Activists in transition : progressive politics in democratic Indonesia - Dibley, Thushara; Ford, Michele; Sastramidjaja, Yatun L. M. (Southeast Asia Program Publications, an imprint of Cornell University Press, 2019)
"Assesses the contribution that nine progressive social movements have made to democratization from the late 1980s and how in turn how each of those movements has been influenced by democratization"--